Underwater archeology - Trejo Rivera, Flor (Mexico, D.F. : Fundacion Cultural Armella Spitalier : Cacciani, S.A. de C.V., 2009)
Explores underwater archeology, a world of submerged cultural and historical remains left to rediscover and preserve.
Includes bibliographical references.
Online resource; title from PDF cover page (Digitalia, viewed December 27, 2016)
Keywords: Underwater archaeology; Underwater exploration; Electronic books